Effectiveness of Sonification of Ketumbar Tip (Coriandrum Sativum L.) for Diabetes Melites Complications on the Gynels with Manly Wistar Rats (Rattus Norvegicus) as Aloksan Induced Coal Animals - Irza Haicha Pratama; Angelika Sio Siagian; Faskanita Maristella Nadapdap; Syahdina Saufa Yardha Chaniago; Laura Novi Silalahi (International Journal of Science and Society, 2023)
The most common microvascular complication is diabetic nephropathy. Coriander is traditionally used as a stimulant, carminative, anticonvulsant, diuretic and antirheumatic, antiemetic and has potential as an antioxidant. Thus, the authors were interested in exploring the effectiveness of coriander seed sonification (Coriandrum sativum L.) on complications of diabetes mellitus in alloxan-induced male rats as experimental animals, especially on kidney micro-vascularization. This study was an experimental study. In this study, sonification of coriander seeds was carried out using a sonicator. All rats in this study were induced by injection of 5% alloxan, then grouped into 5 different groups including: control (Na-CMC), standard (metformin), coriander seed sonification 200 mg/kgBW, 400 mg/kgBW, and 800 mg/kgBW. The measured parameters in this study were GFR and uACR. The results revealed that the coriander seed sonification in this study significantly increased the GFR value and reduced uACR in line with the increase in the administered dose of coriander sonification (p value < 0.05). Hence, it can be concluded that coriander seed sonification has a protective effect against kidney damage due to diabetes.